Chest wall infarction following bilateral internal thoracic harvesting for coronary revascularization in a patient with previous aortic abdominal aneurysm surgery: A rare complication. Issue 11 (27th August 2021) - Lapeze, Joel; Boucher, Fabien; Farhat, Fadi
Abstract: A 75 years old man with previous aortic abdominal aneurysm surgery through a transverse laparotomy underwent bilateral internal thoracic artery to coronary artery bypass grafting. He immediately thereafter developed a severe chest and upper abdominal walls ischemia with metabolic acidosis, and finally deep sternum wound infection and upper abdominal wall necrosis. He benefitted from sternal reconstruction and vaccum assisted treatment, with delayed pectus major flap reconstruction. Chest and abdominal wall infarction following bilateral internal thoracic artery (BITA) harvesting is a very rare but life‐threatening complication. Caution use of BIMA should be in order in patients with inferior epigastric artery flow impairment.